Iowa Birdline update, January 11, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email for the Iowa Birdline update for January 11, 1993. Highlights of the update include sightings of the continued presence of the two Townsend's Solitaires, Long-tailed Duck, Trumpeter Swans and a Prairie Falcon. Also included are handwritten notes for the next week's update with sightings of a first year Iceland Gull and Thayer's Gulls Epson - sheet feed/flatbed